Monitoring Betaine Using Interval Time Between Events Control Chart - Saleem, Muhammad; Khan, Nasrullah; Aslam, Muhammad (Frontiers in Nutrition, 2022)
A generalization of moving average control chart for exponential distribution under classical statistics is presented in this paper. The designing of the moving average control chart for exponential distribution under neutrosophic statistics is presented. A Monte Carlo simulation under neutrosophic is introduced and applied to determine the neutrosophic control limits coefficients and neutrosophic average run length and neutrosophic standard deviation for various shifts. The application of the proposed chart is given using Betaine data. The comparison and real example studies show the efficiency of the proposed chart over the existing charts.